Correlation and path analysis in black and brown seeded soybean [Glycine max (L.) Merr.] genotypes at Melko and Modio, South-Western Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2023)
Sixty-four soybean genotypes were evaluated to study the association among yield and related traits and determine the directions of association. The field experiment was conducted during the main cropping season in 2019 at Jimma and Bonga Southwestern Ethiopia. The experiment was laid with a simple lattice design with two replications. Data were collected on quantitative traits. Analysis of variance showed significant to highly significant differences among genotypes for all of the studied traits. Correlation analysis exhibited that grain yield was positively and significantly associated with harvest index and the number of pods per plant. Harvest index exerted the maximum positive direct effect on grain yield, followed by pod per plant, seed yield per plant at a genotypic level, and these traits could be used for selection to improve grain yield in soybean.Int. J. Agril. Res. Innov. Tech. 13(1): 67-71, June 2023